DEVELOPMENT OF INSURANCE AGENTS IN UKRAINE IN THE CONTEXT OF ITS IMPACT ON EFFECTIVE FUNCTIONING OF THE INSURANCE MARKET - Добош, Назар (Socio-economic relations in the digital society, 2019)
The purpose of the work is to develop theoretical and methodological foundations for improving the state regulation of insurance agents and brokers in Ukraine in the context of the development of the financial and credit system. The authors put and solve the following tasks in the article below: a retrospective study of the development of the market of insurance agents in Ukraine and the substantiation of the theoretical foundations for its functioning, analysis of the legislative and regulatory framework for regulating the insurance agents market in Ukraine and international experience, developing recommendations for improving state regulation of activities insurance agents in Ukraine.
Keywords: insurance service; financial market; insurance mediation; insurance agents and brokers